2021
DOI: 10.1098/rsos.210447
|View full text |Cite
|
Sign up to set email alerts
|

Forensic characteristics and population construction of two major minorities from southwest China revealed by a novel 37 Y-STR loci system

Abstract: Y-chromosome short tandem repeats (Y-STRs) have become important supplementary evidence in forensic science. Nowadays, the Y-chromosome STR haplotype reference database (YHRD) contains abundant Y-STR haplotype data from all over the world, while haplotype data of Guizhou Miao and Tujia are scarce. Hence, genetic polymorphisms of 37 Y-STRs were investigated in 446 unrelated males (206 Miao males and 246 Tujia males) residing in Guizhou Province. A total of 206 and 242 unique haplotypes with the highest diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The 23 reference populations were distributed around the high incidence of EC in China ( Fig. 1 ), including Han_Beijing (n = 114) [ 54 ], Han_Fujian (n = 117) [ 54 ], Han_Guangdong (n = 112) [ 54 ], Han_Guangxi (n = 104) [ 54 ], Han_Shandong (n = 85) [ 54 ], Han_Shanxi (n = 95) [ 54 ], Han_Zhejiang (n = 94) [ 54 ], Han_Jiangxi (n = 108) [ 54 ], Han_Heilongjiang (n = 89) [ 54 ], Han_Hunan (n = 98) [ 54 ], Han_Henan (n = 1411) [ 54 , 55 ], Han_Jilin (n = 88) [ 56 ], Han_Liaoning (n = 566) [ 56 ], Han_Hainan (n = 473) [ 57 ], Han_Shaanxi (n = 430) [ 58 ], Miao_Guizhou (n = 206) [ 59 ], Tujia_Guizhou (n = 246) [ 59 ], Hui_Gansu (n = 146) [ 60 ], Hui_Ningxia (n = 83) [ 60 ], Tibetan_Sichuan (n = 499) [ 61 ], Mongolian_Hohhot (n = 226) [ 62 ], Mongolian_Hulunbuir (n = 223) [ 62 ] and Mongolian_Ordos (n = 200) [ 62 ]. We calculated Φ PT and corresponding P values using AMOVA to provide a valid measure of population genetic differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 23 reference populations were distributed around the high incidence of EC in China ( Fig. 1 ), including Han_Beijing (n = 114) [ 54 ], Han_Fujian (n = 117) [ 54 ], Han_Guangdong (n = 112) [ 54 ], Han_Guangxi (n = 104) [ 54 ], Han_Shandong (n = 85) [ 54 ], Han_Shanxi (n = 95) [ 54 ], Han_Zhejiang (n = 94) [ 54 ], Han_Jiangxi (n = 108) [ 54 ], Han_Heilongjiang (n = 89) [ 54 ], Han_Hunan (n = 98) [ 54 ], Han_Henan (n = 1411) [ 54 , 55 ], Han_Jilin (n = 88) [ 56 ], Han_Liaoning (n = 566) [ 56 ], Han_Hainan (n = 473) [ 57 ], Han_Shaanxi (n = 430) [ 58 ], Miao_Guizhou (n = 206) [ 59 ], Tujia_Guizhou (n = 246) [ 59 ], Hui_Gansu (n = 146) [ 60 ], Hui_Ningxia (n = 83) [ 60 ], Tibetan_Sichuan (n = 499) [ 61 ], Mongolian_Hohhot (n = 226) [ 62 ], Mongolian_Hulunbuir (n = 223) [ 62 ] and Mongolian_Ordos (n = 200) [ 62 ]. We calculated Φ PT and corresponding P values using AMOVA to provide a valid measure of population genetic differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 15 reference populations were included for population genetic structure analysis, including Han_Beijing (n = 114) [ 54 ], Han_Guangxi (n = 104) [ 54 ], Han_Jiangxi (n = 108) [ 54 ], Han_Liaoning (n = 556) [ 56 ], Han_Hainan (n = 473) [ 57 ], Han_Shaanxi (n = 430) [ 58 ], Miao_Guizhou (n = 206) [ 59 ], Tujia_Guizhou (n = 246) [ 59 ], Hui_Gansu (n = 146) [ 60 ], Mongolian_Hohhot (n = 226) [ 62 ], Mongolian_Hulunbuir (n = 223) [ 67 ], and Mongolian_Ordos (n = 200) [ 67 ]. Our analysis showed that the frequency of the DYS393*12 allele was 0.44 in the EC high-risk population in Henan, while the rest of the EC population and the EC high-risk population possessed the high-frequency alleles DYS389I*12 and DYS393*12 (frequencies ≥0.5).…”
Section: Resultsmentioning
confidence: 99%
“…Population genetic analyses of Guizhou Dong and 16 reference populations are conducted by the following methods. Firstly, analysis of molecular variance (AMOVA) is used to estimate genetic distances ( R ST ) between the Guizhou Dong group and other populations (Guizhou Bouyei ( Luo et al, 2019 ), Yunnan Dai, Hunan Dong ( Shu et al, 2015 ), Guizhou Han ( Sun et al, 2019 ; Zhou et al, 2016 ), Yunnan Han ( Kwak et al, 2005 ; Yanmei et al, 2010 ; Yin et al, 2022 , 2020 ), Yunnan Hui ( Xie et al, 2019 ), Guizhou Miao ( Tang et al, 2020 ; Luo et al, 2021 ), Hulunbuir Mongolian ( Wang et al, 2019 ), Sichuan Qiang, Qinghai Salar ( Zhu et al, 2007 ), Qinghai Tibetan ( Zhu et al, 2008 ; Cao et al, 2018 ), Guizhou Tujia, Guizhou Yi ( Song et al, 2021 ), Yunnan Yi ( Zhu et al, 2006 ; Fan et al, 2019 ), Gansu Yugur and Guangxi Zhuang ( Wang et al, 2022 ; Guo et al, 2017b ) by the online tool YHRD. Next, the phylogenetic tree of these populations is constructed by the MEGA v7.0 software ( Kumar, Stecher & Tamura, 2016 ) with the method of Neighbor-Joining based on their pairwise R ST values.…”
Section: Methodsmentioning
confidence: 99%